An emic towards well-being - Mahbub, Amina; Roy, Rita Das (BRAC Research and Evaluation Division (RED), 2019)
Usually much attention has not been paid to people's perspective towards their own wellbeing in the nation level. In fact it is rare to find national level studies on realities about people's well-being and People's idea in the development process usually are not considered (UNDP, 1996). But people are conscious about their own well-being and they have a transparent idea about their need and priorities as well. The present study is a part of BRAC-ICDDR, B joint research project. The main objectives of the research project is to assess the effect of BRAC and lCDDR, B interventions on health status and human wellbeing and also to explore the pathways and causal mechanism through which these development efforts influence (Chowdhury and Bhuiya, 1995). Since the impact of the development interventions on the well-being of individuals and families in rural Bangladesh is primarily concerned here; to get an outlook about what is 'well-being' to the people is very much crucial to be identified.